A decoupled SPH-FEM analysis of hydrodynamic wave pressure on hyperbolic-paraboloid thin-shell coastal armor and corresponding structural response. (1st October 2022) - Wu, Gaoyuan; Garlock, Maria; Wang, Shengzhe
Highlights: Decoupled numerical scheme of smoothed particle hydrodynamics (SPH) and finite element modeling (FEM) presented for wave-shell interaction. Hydrodynamic wave pressure on hyperbolic paraboloid (hypar) geometries studied. Structural dynamic analysis of hypar-shaped thin shell coastal armor against regular waves. Applicability of Goda's formula evaluated for hypar-shaped thin shell coastal armor. Abstract: Kinetic Umbrella, an innovative thin-shell structural system, incorporating hyperbolic paraboloid (hypar) geometry, has been proposed for coastal hazard mitigation. Its feasibility against surge and wave loadings has been conceptually validated via a Hurricane Sandy case study. However, the typical hydrodynamic wave pressure on hypar geometries and the rationality of the previously conducted static structural analyses remain unknown. In response, this paper implements a decoupled numerical scheme consisting of smoothed particle hydrodynamics (SPH) and finite element modeling (FEM), investigating the hydrodynamic wave pressure and corresponding structural response via structural dynamic analyses. Furthermore, the accuracy of applying the hydrodynamic wave pressure predicted by the well accepted Goda's formula to the structural analysis of Kinetic Umbrellas is also evaluated. The results show that the hydrodynamic wave pressure on hypar follows a bilinear like shape along height and increases gradually from the edge of the hypar to the longitudinal spine. The hydrodynamic wave pressure difference between the edge and the longitudinal spine will be intensified by higher warping magnitude of hypar and under breaking waves. For structural response, the maximum displacement and the maximum tensile membrane force of the shell are significantly underestimated by static analyses with Goda's formula, implying the necessity of implementing the decoupled SPH-FEM scheme with structural dynamic analyses. For other critical demands, the difference is mostly smaller than 20%. The findings reinforce the idea that hypar thin shells are structurally feasible under surge and wave loadings, and ultimately facilitate the employment of hypar thin shells for coastal defense as a sustainable alternative to traditional coastal structures.